The Changes in English in the Early Modern Period and the Impact of Printing Technology on the Spread of the Language - Izza, Ana Nurul; Azarian, Andyka Ariella Keanu; Awali, Ar’Rafi Jamru (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The Early Modern English period (c. 1500–1700) was a time of significant linguistic transformation, driven by the social, political, and technological changes. One of the most crucial factors of influencing the spread and standardization of English was the rise of printing technology, introduced by William Caxton in 1476. This study aims to examine the linguistic changes of periodic english particularly in vocabulary, grammar, and spelling and analyze how the printing press contributed to the spread and stabilization of English. This study employs a historical linguistic method and uses primary sources, including printed texts, dictionaries, and grammar books from the era. to track the shifts in language. The findings reveal that the standardization of spelling and grammar was largely influenced by the increased availability of printed materials such as literature, which helped to establish a more uniform version of English. Additionally, the spread of literacy to the masses and the wider circulation of texts accelerated the adoption of new words, many borrowed from Latin and other European languages. Ultimately, printing technology played a pivotal role in shaping Modern English by promoting consistency and accessibility. The study underscores the connectiness of technological advancements and linguistic evolution during the time.